APPLICATION OF RESTORATIVE JUSTICE TO DRUGS CASES OF POTENT DRUG LIST G CLASS 2 - Elang Prasetyo; Taufik Makarao; Fauziah Fauziah (Jurnal Hukum Jurisdictie, 2023)
The concept of Restorative Justice has actually been around for quite some time, more than twenty years ago as an alternative settlement of criminal cases, especially children, with various considerations. As stated by John Braithwaite that, Restorative Justice is a new direction between "justice" and "walfare model", then between "retribution" and "rehabilitation". Restorative justice is a settlement process that is carried out outside the criminal justice system by involving victims, perpetrators, victims' families and perpetrators' families, the community and parties with an interest in a criminal act that occurred to reach an agreement and settlement. The problem of hard drugs is a serious problem in the world of health. People who do not know become victims. Even though it is not certain that the drug being abused is correct and the composition is correct. Obviously this is very dangerous for patients or users of certain brands of drugs, especially hard drugs (list G drugs) which contain active ingredients, can cause dependence, because other than drugs if used improperly or without a doctor's prescription, on the contrary, they will become toxic to the human body and endanger health. . The formulation of the problem is as follows: (1) How is the urgency of justice in the implementation of Restorative Justice in cases of hard drugs listed G Group 2? (2) How effective is the implementation of the implementation of the application of Restorative Justice in cases of hard drugs listed G Group 2? The research method used is normative juridical with data collection techniques using library research and document studies and data analysis techniques using normative analysis methods. The results of the study show that: (1) The Restorative Justice approach can help to reduce the abuse of hard drugs listed G Group 2 in a more effective way, through recovery of perpetrators and their return to society. In this case, the Restorative Justice approach can also help to build a safer and healthier environment for the community. (2) Based on existing research, it can be concluded that regulations have good effectiveness in implementing restorative justice in drug cases belonging to group G. The restorative justice approach prioritizes recovery and rehabilitation of offenders, offering opportunities for offenders to improve themselves and return to being a good member of society. contribute. Therefore, restorative justice arrangements for drug cases belonging to group G not only provide a deterrent effect for perpetrators, but also provide opportunities for self-improvement and reintegration into society as activists.